The Role of Insulin Receptor Isoforms in Diabetes and Its Metabolic and Vascular Complications - O. Escribano; N. Beneit; C. Rubio-Longás; A. R. López-Pastor; A. Gómez-Hernández (Journal of Diabetes Research)
The insulin receptor (IR) presents by alternative splicing two isoforms: IRA and IRB. The differential physiological and pathological role of both isoforms is not completely known, and it is determinant the different binding affinity for insulin-like growth factor. IRB is more abundant in adult tissues and it exerts mainly the metabolic actions of insulin, whereas IRA is mainly expressed in fetal and prenatal period and exerts mitogenic actions. However, the change in the expression profile of both IR isoforms and its dysregulation are associated with the development of different pathologies, such as cancer, insulin resistance, diabetes, obesity, and atherosclerosis. In some of them, there is a significant increase of IRA/IRB ratio conferring a proliferative and migratory advantage to different cell types and favouring IGF-II actions with a sustained detriment in the metabolic effects of insulin. This review discussed specifically the role of IR isoforms as well as IGF-IR in diabetes and its associated complications as obesity and atherosclerosis. Future research with new IR modulators might be considered as possible targets to improve the treatment of diabetes and its associated complications.